Deployable structures demonstrator StrathSat-R : A second chance - Parry, Thomas; Brown, Roy Hutton; Hammond, Paul; Clark, Ruaridh; Garcia Yarnoz, Daniel (2014)
StrathSat-R is an experiment proposed for ESA/DLR's REXUS13 sounding rocket campaign to validate different inflation deployment techniques in space conditions. The primary objective was to deploy and validate two structures in micro-gravity and near vacuum conditions by using residual air inflation. The experimental setup consisted of two CubeSat-based ejectables, the first of them deploying a pyramidal structure that can be used for passive orbit transfer and de-orbiting, and the second containing a morphing inflatable with multiple cells, which will actively modify its shape during flight by using pumps connected to cells to alter the distribution of air. StrathSat-R was originally selected to be launched from Esrange Space Centre in Kiruna on board of the REXUS13 rocket in May 2013. Unfortunately, due to a procedural omission by the launch service provider, the two ejectable sections of the StrathSat-R experiment were not ejected during flight and remained inside the rocket. The experiment did perform nominally and recorded the flight, but could not carry out its experimental goals without ejection. Therefore, a second launch opportunity was granted to the team with the experiment launched once again on REXUS15 in May 2014. This paper presents the design changes and improvements made in the different subsystems between both launches, as well as the results of the second sounding rocket flight. The new experiment presents a more robust and reliable electronic subsystem, avoiding problematic components in the original design, and includes slight modifications in the design and the fabrication procedures of the two inflatable structures. The recovery system, comprising a GPS receiver, a Globalstar antenna and an RF beacon, has also undergone a series of, mainly software, improvements. This particular subsystem was critical to mission success, enabling the recovery of the ejectables after flight, and hence will be a focus of the paper. Finally, a new ground segment interface software has been implemented with the ...